Iptek Pengembangan Sistem Informasi Akademik Menggunakan Web Responsive PHP dan Database Mysql di SMK Negeri 8 Padang - Putra, Teguh Ikhsani (Universitas Negeri Padang, 2022)
This study aims to master the validity, practicality and effectiveness of Academic Information System Development using a Responsive PHP Website and MySQL Database. In Vocational High Schools (SMK) N 8 Padang, this research stage is Research and Development (R&D). The research procedure using this analytical model is the development of the main stages 4- D, namely Define (Definition), Design (design), Develop (development), and Disseminate (spread) the main steps in the study are not in accordance with the original but are adjusted to the characteristics of the subjects and place of origin of test takers. The trial was tested on 6 teachers and 30 students at State Vocational High School (SMKN) 8 Padang. Starting from the research that tried to validate the totality, the results were 91, the practicality inverse test results for the totality of 98% were 90.97%, and the results of the totality effectiveness test were 91.6%.